Challenges In Telemedicine Implementation For Pregnancy Care During The Covid-19 Pandemic - Yuliana Yuliana (Poltekkes Kemenkes Surakarta, 2020)
Background: COVID-19 pandemic condition made the consultation shifted from face to face consultation to telemedicine for mild, stable, and follow up cases. In stabile condition of pregnant patients, telemedicine implementation will be beneficial to reduce the COVID-19 transmission risk. The problems are not all patients can implement telemedicine and the reimbursement procedure was hard. The aim of this paper is to describe about challenges in telemedicine implementation for pregnancy care during the COVID-19 pandemic. Methods: this paper is a literature review, Literature was identified from the archives of PubMed, Scopus, and Elsevier. All the literature was published in 2020. The inclusion criteria were the literature should be peer-reviewed and related to the topic of the paper. Keywords were challenges, COVID-19, opportunities, pregnancy, and telemedicine. Results: from 18 articles in this literature review, it was found that challenges in telemedicine are reimbursement, infrastructure, confidentiality, and unfamiliarity for the pregnant patients. Conclusion: Telemedicine can be used for pregnant patient control consultation during the stable condition to minimize the risk of COVID-19 transmission. The implication of this paper is to give insight that telemedicine can be done for stable pregnancy condition to reduce the risk of COVID-19 transmission during the pandemic. The benefits of reducing COVID-19 risk transmission for baby and mother outweigh the challenges and problems such as reimbursement, confidentiality, and technical issues.